A mathematical model of animal-human Brucellosis transmission in Armenia: Implications for prevention and control - Uchenna Anyanwu; Yuqian Wang; Alexandra Walker; Artemiy Dimov; Jakob Zinsstag; Youssef Akladios; Nakul Chitnis; Sandra Volken; Binyu Li; Lusine Paronyan; Ani Manukyan; Jon Simonyan; et al. (CABI One Health)
Abstract Brucellosis, a zoonotic disease impacting public health and economies, is prevalent in several countries, particularly low- and middle-income regions. This study centers on Armenia, where the Veterinary Department of the Food Safety Inspection Body employs a test-and-slaughter strategy to control the disease. A dynamic deterministic compartmental model was constructed using seropositive reported data from humans and livestock (cattle and sheep) from 2019 to 2021. The model simulates the effects of enhanced test-and-slaughter strategies from 2022 to 2031 on brucellosis transmission among sheep, cattle, and humans. The results suggest that an increase in testing and slaughter rates leads to a decrease in infected populations among both humans and livestock. Approximately 65% of the human brucellosis cases are a result of sheep-to-human transmissions. This reduction in infected populations is expected to subsequently lower the overall transmission rates in livestock and humans. However, even with the highest coverage levels (75% for sheep and 90% for cattle), infections in humans and livestock are projected to persist. The study highlights the need for a One Health approach that integrates mathematical modeling with public health intervention strategies. While the upgraded test-and-slaughter strategy could prove effective, an economic analysis of the predicted cumulative incidence in humans and livestock prevalence could guide decision making processes. Compensation for culled animals is a critical factor. The success of the intervention relies on collaboration between veterinary and public health sectors, community engagement, and awareness campaigns. One Health impact statement This study applied a mathematical model to investigate brucellosis transmission within the livestock population and from animals to humans. It assessed the impact of different test-and-slaughter coverage levels from 2022 to 2031 on disease burden and livestock populations. Although the research did not encompass the entire One Health spectrum, it shed light on the potential benefits of integrating human and animal health interventions. Local institutions (such as the Food Safety and Inspectorate Body and the National Centre for Disease Control in Armenia) and international collaboration among scientists contributed to a better understanding and controlling zoonotic diseases. The findings offer valuable insights for decision making, aiding Armenian policy makers in effectively managing brucellosis and enhancing public health, food safety, and monetary savings. Furthermore, the research provides a basis for further exploration in this field.